Community, State and Questions of Social Evolution in Marx’s "Ethnological Notebooks" - Gailey, Christine Ward (Anthropologica, 2022)
Marx’s Ethnological Notebooks were among the last of his writings. They comment upon class and state for mation in a range of precapitalist contexts. The argument presented here is that after Capital, Marx turned to problems of class formation in socialism, examining the conflict between communities of producers and state agendas, on the one hand, and the entrenchment of bureaucracies and state functionaries, on the other. The commentaries distance Marx from state theories of social evolution: certain social forms may persist and change in opposition to the state, at the same time defending more egalitarian practices.